Proses Berpikir dalam Memecahkan Masalah Trigonometri Ditinjau dari Gaya Kognitif Reflektif dan Impulsif Siswa - Muhammad Ade Syam Agung; Suradi; Ilham Minggi (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2023)
This research aims to describe students' thinking processes in solving trigonometry problems in terms of reflective and impulsive cognitive styles. It is a descriptive study with a quantitative and qualitative approach. The subjects in this research were four students from the 11th grade of a high school, two students in each group representing the reflective and impulsive cognitive styles based on their results in the trigonometry problem-solving test. Data were collected through tests and interviews. The instruments used for data collection included trigonometry problem-solving tests, MFFT cognitive style tests, and interview guidelines. The results of this research indicate that: (1) Students with a reflective cognitive style and high scores in the trigonometry problem-solving test (SRT)tend to undergo an assimilation process, reaching equilibrium at each stage of problem-solving. (2) Students with an impulsive cognitive style and high scores in the trigonometry problem-solving test (SIT) also experience an assimilation process, reaching equilibrium, but undergo accommodation during the stage of planning problem-solving strategies. (3) Students with both reflective and impulsive cognitive styles and low scores in the trigonometry problem-solving test (SRR and SIR) tend to be in a state of disequilibrium, unable to integrate the existing schemes in their minds with their knowledge.